Left extralobar pulmonary sequestration and a right aorto-to-pulmonary vein fistula in a newborn: a 3-mm thoracoscopic monolateral approach. (5th July 2018) - Macchini, Francesco; Gentilino, Valerio; Leva, Ernesto; Rothenberg, Steven
Abstract: An extralobar pulmonary sequestration (EPS) associated with a contralateral aorto-to-pulmonary vein fistula is rare. We report the case of a female newborn with left EPS fed by an artery originating from the distal thoracic aorta and, symmetrically on the controlateral side, an artery shunting in the inferior right pulmonary vein. Echocardiography showed dilatation of the left atrium. On the 34th day since birth (weight 4500 g), the patient was operated on thoracoscopically. The EPS was closed with a 3-mm sealing system, divided and removed. A window in the mediastinal pleura was created, and the origin of the fistula was identified and sealed. The postoperative course was uneventful. The patient was discharged on Day 4 with no echocardiographic signs of persistence of the fistula and of the congestive heart failure. This is the first case report of a thoracic large systemic circulation-to-pulmonary vein fistula causing heart failure associated with EPS. The thoracoscopic monolateral approach and the availability of 3-mm instruments guaranteed a maximum level of minimal invasiveness.